Slow and stopped light in metamaterials: The trapped rainbow - K. L. Tsakmakidis; Hess, O. (Proceedings of SPIE - The International Society for Optical Engineering, 2008)
We show how guided electromagnetic waves propagating along an adiabatically tapered negative-refractive-index metamaterial heterostructure can be brought to a complete halt. It is analytically shown that, in principle, this method simultaneously allows for broad bandwidth operation (since it does not rely on group index resonances), large delaybandwidth products (since a wave packet can be completely stopped and buffered indefinitely) and high, almost 100%, in/out-coupling efficiencies. By nature, the presented scheme invokes solid-state materials and, as such, is not subject to low-temperature or atomic coherence limitations. A wave analysis, which demonstrates the halting of a monochromatic field component travelling along the heterostructure, is followed by a pertinent ray analysis, which unmistakably illustrates the trapping of the associated light-ray and the formation of a double light-ray cone ('optical clepsydra') at the point where the ray is trapped. This method for trapping photons conceivably opens the way to a multitude of hybrid optoelectronic devices to be used in 'quantum information' processing, communication networks and signal processors and may herald a new realm of combined metamaterials and slow light research.